2008
DOI: 10.1007/s00467-008-0892-0
|View full text |Cite
|
Sign up to set email alerts
|

Short PET in pediatric peritoneal dialysis

Abstract: Peritoneal equilibration test (PET) is a common technique used in children to evaluate peritoneal membrane transport capacity and adequate the dialysis regimen. Considering that this is a laborious test, a shortened version has been proposed. Our goal was to evaluate the concordance between the 2-h (short) and 4-h (classical) PET values to determine whether the short PET could be used in the clinical setting. Eighty-one PET corresponding to 81 peritoneal dialysis patients from two pediatric nephrology centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The authors found that in all patients, the peritoneal transport categories were the same using PET values at 2 and 4 h of the procedure. Later on, in 2007, we conducted another retrospective evaluation of the short PET in 81 patients from two different local medical centers [16] and found no significant correlation between values at 2 and 4 h, suggesting that the use of the short test was not reliable enough to estimate the transport capacity of the peritoneal membrane in a pediatric population.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors found that in all patients, the peritoneal transport categories were the same using PET values at 2 and 4 h of the procedure. Later on, in 2007, we conducted another retrospective evaluation of the short PET in 81 patients from two different local medical centers [16] and found no significant correlation between values at 2 and 4 h, suggesting that the use of the short test was not reliable enough to estimate the transport capacity of the peritoneal membrane in a pediatric population.…”
Section: Discussionmentioning
confidence: 93%
“…These authors concluded that short PET was sufficiently reliable to replace the 4-h version, without meaning a change in the depuration or ultrafiltration category of the patient. Later on, we published a retrospective PET experience in 81 patients, showing a weak concordance between the 2 and 4-h PET results [16]. Therefore, current recommendations are based on retrospective experiences with controversial results.…”
Section: Introductionmentioning
confidence: 98%
“…Cuevas et al (16) conducted a prospective study of the results of 81 PET tests in 81 patients. They analyzed the results collected after 4 h (t-PET) and after 2 h (mini-PET) for glucose and creatinine and did not find a correlation between the results.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, dwell time of 2 hours provides reliable results and time-saving procedure for the health care personnel and it could be used for the clinical assessment of the patients [5,[10][11][12]. In contrast, a study in children found no correlation between 2-hour and 4-hour dwell times and the authors reported that short testing procedure would not be reliable in pediatric population for the assessment of peritoneal membrane functions [13].…”
Section: Discussionmentioning
confidence: 99%